2021
DOI: 10.1186/s12879-020-05742-9
|View full text |Cite
|
Sign up to set email alerts
|

The HIV care cascade for adolescents initiated on antiretroviral therapy in a health district of South Africa: a retrospective cohort study

Abstract: Background Little evidence exists to comprehensively estimate adolescent viral suppression after initiation on antiretroviral therapy in sub-Saharan Africa. This study examines adolescent progression along the HIV care cascade to viral suppression for adolescents initiated on antiretroviral therapy in South Africa. Methods All adolescents ever initiated on antiretroviral therapy (n=1080) by 2015 in a health district of the Eastern Cape, South Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 19 publications
6
54
0
Order By: Relevance
“…Therefore, young people living with HIV constitute a growing and key sub-population of people living with HIV globally. The increase in HIV prevalence amongst adolescents (10 to 19 years) is the result of the generation of children infected with HIV perinatally who are surviving into adolescence because of improved access to antiretroviral treatment (ART), and increased HIV incidence as a result of risky (sexual) behaviour in this age group [3,4]. Despite tremendous gains in the reduction of over-all AIDS-related deaths to the tune of 43%, AIDS-related deaths amongst adolescents in Eastern and Southern Africa have increased in the last decade [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, young people living with HIV constitute a growing and key sub-population of people living with HIV globally. The increase in HIV prevalence amongst adolescents (10 to 19 years) is the result of the generation of children infected with HIV perinatally who are surviving into adolescence because of improved access to antiretroviral treatment (ART), and increased HIV incidence as a result of risky (sexual) behaviour in this age group [3,4]. Despite tremendous gains in the reduction of over-all AIDS-related deaths to the tune of 43%, AIDS-related deaths amongst adolescents in Eastern and Southern Africa have increased in the last decade [5].…”
Section: Introductionmentioning
confidence: 99%
“…Screening titles and abstracts identi ed 66 studies for full-text examination, of which 32 studies met the inclusion criteria and were included. Bibliography review identi ed two additional studies, making a total of 34 studies included in the review (Figure 1) Twenty-nine of the 34 included studies were conducted in and/or had data collected from sub-Saharan Africa (SSA) countries, including South Africa [21][22][23][24][25][26][27][28][29][30][31],…”
Section: Resultsmentioning
confidence: 99%
“…Of 11 studies from South Africa, four were conducted in Cape Town, reporting relatively high VL coverage of 72-89% [22,[24][25][26]. Other studies were conducted in KwaZulu-Natal [21,30,31], Eastern Cape [23,27] and Gauteng [29], and another study [28] included data from ART patients in nine different provinces across the country. Studies with interventions to improve quality of ART program had a VL coverage of >90% whilst other studies reported a VL range of 25%-81%.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative interviews were self-administered using standardised questionnaires on tablet devices. Available viral load data were extracted from participants' clinical records and linked to their questionnaire data [33,34]. This analysis was restricted to adolescents who acquired HIV perinatally (APHIV) (Figure 1) determined by ART initiation age 10-years or younger and validated using other supporting evidence such as history of parental death, maternal HIV-status and self-reported sexual history [33,35].…”
Section: Study Populationmentioning
confidence: 99%
“…Available viral load data were extracted from participants' clinical records and linked to their questionnaire data [33,34]. This analysis was restricted to adolescents who acquired HIV perinatally (APHIV) (Figure 1) determined by ART initiation age 10-years or younger and validated using other supporting evidence such as history of parental death, maternal HIV-status and self-reported sexual history [33,35]. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review)…”
Section: Study Populationmentioning
confidence: 99%